Profil Keputusan Struktur Modal Pelaku Usaha Mikro, Kecil Dan Menengah - Lusianus Kelen; Alliny N. R. Hutar; Vindya D. Adindarena; Yuniarti R. Renggo (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
Research on capital structure so far has often been studied in the context of large companies and there are still few studies that explain it in the context of Micro, Small and Medium Enterprises (MSMEs). Not only that, research on capital structure has so far been dominated by research with a regression-based model and focuses on business characteristics, not individuals. In addition, the development of capital structure in Indonesia is also dominated by research from Java. This has become the author's interest in researching the capital structure of MSMEs in areas outside Java, more precisely in East Sumba Regency, East Nusa Tenggara Province (NTT). By using quantitative descriptive data analysis techniques on 208 samples of actors as long as MSME owners in East Sumba Regency, the results show that the capital structure decision profile of MSME actors in East Sumba follows the pecking order theory pattern, where MSMEs prioritize internal funding over external funding. However, this theory is not the only one in explaining the profile of capital structure decisions, because the trade-off theory is also illustrated even though the percentage is small.